Sistem Informasi Pariwisata Kabupaten Merangin - Indria, Lily; Assegaff, Setiawan (LPPM Universitas Dinamika Bangsa, 2023)
Currently there is not enough information about tourist objects in Merangin Regency so not many tourists and the public know what tourist objects are in Merangin Regency. Therefores, this needs to be overcome by providing more complete and detailed information using web-based information media. The purpose of this research is to make it easier for tourists to find any tourist information in Merangin district. The research method used was to collect data through literature studies, interviews, and observations, as well as analyzing software requirements, building a database using the UML (Unified Modeling Language) method. This research produced a web-based Merangin district tourism information system and was made only as a prototype.